A CASE STUDY ON LEADING INDICATORS FOR OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT PRACTICES BY HEALTHCARE WORKERS OF PUBLIC AND PRIVATE HOSPITALS OF GUJARAT - Patel, Kesha; Patel, K.K; Jani, Kinjal; Khatri, Twinkle (ShodhKosh: Journal of Visual and Performing Arts, 2024)
BACKGROUND: An Occupational Health and Safety Management System is a fundamental part of an organization's risk management strategy. Implementing an OHSMS helps an organization protect its workers and others within its control, helps with legal requirements, and facilitates ongoing improvement. METHOD: the study used an exploratory research design. It was carried out in randomly selected public and private hospitals of Gujarat. 503 healthcare workers were taken for the study using the simple random sampling method. Descriptive statistics and factor analysis were applied to fulfill the objectives of the study. RESULT: Leading indicators are something that can help health personnel to minimize the risk of any unwanted incident before its occurrence. The majority of these indicators are proactive, predictive, and input-oriented. These are quite tough to measure, but they are much easier to influence. Leading indicators are classified based on organization, system, and behavior. CONCLUSION: The leading indicators for occupational health are to be finding out for preventing the incidence at the workplace due to negligence of the employees and employers as well. There is a factor that implies the need for occupational health policy at the health care centers. Occupational health is not only for health care but applied to all other sectors but this study only focuses on the field of health care.